Effect of lectin from artocarpus heterophyllus seed on cancer cell lines - Mohd Ali, Zuraidah; Abdul Munaim, Mimi Sakinah; Wan Sulaiman, Wan Mohd. Azizi (Elsevier, 2014)
The objective of this paper to present cytotoxic effect of jacalin, a purified protein and crude protein from A.heterophyllus seed against cancer cell, human breast cancer (MCF7) and non-small lung carcinoma (H1299). The extraction and purification were carried out by phosphate buffer precipitation and reverse miceller, respectively. MTT and trypan blue exclusion methods were performed to study the cytotoxic activity. Jacalin and crude protein was compared in cytotoxic activity against MCF7 and H1299 cancer cells and the result showed jacalin more effective than crude protein, 64.73 and 75.54 percent for MCF7 and 67.71 and 68.39 percent for H1299, respectively. Jacalin also found very active against MCF7 compared to H1299 cancer cells and expected IC50 for both cancer cells would be reached if concentration of jacalin will extended in cytotoxic activity analysis. Keywords: Artocarpus heterophyllus, jacalin, crude protein, cytotoxicity,cancer cell, MCF7, H1299